Prenatal diagnosis of dicentric chromosome X mosaicism: a case report and review - Wang, Rong Hua; Wu, Ke; Hu, Xiao Ling (Frontiers in Genetics, 2024)
A dicentric chromosome is an abnormal chromosome with two centromeres on the same chromosome. It has been reported that dicentric chromosomes are specific biomarkers of radiation exposure, but dicentric chromosomes are rarely identified in newborns with multiple congenital anomalies. At 16 weeks of gestation, a 39-year-old pregnant woman (gravida 2, para 1) was referred to the prenatal diagnosis center for genetic counseling. The fetal ultrasonography indicated multiple anomalies. Subsequently, amniocentesis was performed, and the G-banding karyotype analysis showed a rare type of mosaicism. The C-banding karyotype analysis indicated a pseudo-dicentric chromosome X [psu dic (X; 18) (p11.2; p11.2)]. A single-nucleotide polymorphism array (SNP array) revealed three pathogenic copy number variations (CNVs). After genetic counseling, the parents chose to terminate this pregnancy. This study provides new evidence for a better understanding of the diagnosis of dicentric chromosomes and emphasizes on the importance of genetic counseling.